Father as a recipient of social service: historical experience in social worker’s professional communication - Eidukevičiūtė, Julija (Information & Media, 2018)
Each community has social groups that are not affected by the measures of common social policy that help in ensuring family welfare. In those cases, families need an individual social worker’s help in order to integrate into the society, overcome exclusion and poverty. The modern approach to the family as the most important to a child and responsible for his/her social development, and therefore the relationship of the social workers with the family in the process of providing aid should essentially differ from that of the Soviet family welfare system, when the parents had to comply with the norms established by the state, comply with the state-defined ideology. The article aims to discuss how a social worker provides help to a man-father by constructing an interaction with the whole family. The article is built on a qualitative hermeneutical and methodological perspective, which allows us to highlight the importance of social communication and historical experience in the process of family help. Keywords: fatherhood, social work, hermeneutics